Intracellular doppler spectroscopy of live tissue sentinels for a fast in-vitro bacterial infection assay - Dawith Lim; Zhen Hua; Fernanda da Cunha; John Turek; Michael Ladisch; David Nolte (Scientific Reports)
Abstract Living organisms are frequently used as sentinels to monitor changes in the environment, and organoids can serve a similar function as in vitro sentinels detecting microbiological processes. One such process of great interest is pathogenic infection, which causes alterations in the cellular dynamics of the sentinels. Doppler light scattering is well suited to measure such changes, as it is sensitive to the intracellular dynamics of the organoids even when the microbe density is too dilute to detect directly. In this paper, we present measurements of the endogenous changes of intracellular dynamics of DLD organoids (microclusters) in response to bacterial infection, detected using a long-coherence form of biodynamic imaging (BDI), a dynamic-contrast digital holography technique that captures the Doppler shifts encoded in the dynamic speckles. With a stable common-path digital holography system and using small in-vitro tissue microclusters, clinically relevant inoculum doses as low as 100 cfu/mL cause detectable changes in intracellular Doppler spectra within hours of infection and several hours before the proliferating bacteria population causes direct light scattering. Because it can measure effects for small bacterial populations, the method shows promise as a fast diagnostic tool to detect the presence of bacteria in patient fluid samples faster than traditional methods.